Pengaruh Corporate Social Responsibility, Profitabilitas, Struktur Modal terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia Peridoe Tahun 2018 - 2022 - Alfiadin, Ardian; Susilo, Dwi Ermayanti; Purnomo, Herry; Muryani, Endang; Ardiansyah, Tedy; Suhartono, Edy (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Company value is important because it influences the company's survival in the future. Many variables can influence company value, such as disclosure and capital structure management. Disclosure is carried out to provide information to stakeholders about the company, one of which is disclosure of Corporate Social Responsibility (CSR) which is a responsibility in terms of economic, environmental and social aspects. Capital structure management is carried out to achieve a balance between liabilities and equity so as to maximize company value. This research aims to determine the influence of Corporate Social Responsibility, Profitability and Capital Structure on Company Value in the current Covid 19 pandemic era. This research uses quantitative descriptive research. The population and sample in this study are pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. The data used is secondary data from annual financial reports on the Indonesia Stock Exchange. This research uses data analysis techniques such as multiple regression analysis and SPSS as tools to process and test data. The results of this research show that partially CSR has no significant effect, ROE has a significant effect and DER has no significant effect on company value. Meanwhile, simultaneously CSR, ROE, and DER have a significant effect on company value.